Gradual or abrupt? Changes in water source of Lake Turkana (Kenya) during the African Humid Period inferred from Sr isotope ratios. (15th October 2017) - van der Lubbe, H.J.L.; Krause-Nehring, J.; Junginger, A.; Garcin, Y.; Joordens, J.C.A.; Davies, G.R.; Beck, C.; Feibel, C.S.; Johnson, T.C.; Vonhof, H.B.
Highlights: Strontium isotope ratios of Lake Turkana reflect the runoff balance of various rivers. Strontium isotopes document large changes in water source areas over the last 14 kyrs. Relative contribution of the SW rivers was enhanced during the African Humid Period. Lake level declined abruptly, while the rainfall locus moved gradually northwards. Rainfall changes appear controlled by E-W adjustments in atmospheric circulation.